Ag+ and Ca+ single implantation and co-implantation induced the cell growth and antibacterial activity of TiN/Ti-6Al-4V. (January 2023) - Zhao, Mengli; Ji, Xingming; Li, Dejun
Abstract: In order to inhibit titanium alloy's (Ti-6Al-4V) release of toxic ions (e.g., V 4+ and Al 3+ ) in the humoral environment, titanium nitride (TiN) film was first coated on Ti-6Al-4V in this paper. Then, silver (Ag) and calcium (Ca) ions were single implanted or co-implanted into the TiN flim respectively to provide significant effects on the osteogenic enhancement and antibacterial responses of TiN film. The results showed that the roughness, hydrophilicities and protein adsorption capacities of samples were all increased after ion implantation. In addition, compared with the single performance improvement over single ion implantation, the Ag + Ca ions co-implanted TiN sample (Ag/Ca-TiN) showed the best cell adhesion, cell proliferation and excellent antibacterial activity. And the study of bacteria-cell co-culture showed that Ag/Ca-TiN could help cells overcome bacteria and occupy the sample surface. These results indicate that the synergy obtained by double ions via co-implantation is the key factor in the osteogenic and antibacterial enhancements. Highlights: Ag + Ca ions were single and co-implanted into TiN/Ti-6Al-4V via PIII&D system. PIII treatment improves the corrosion resistance of TiN. Ag/Ca-TiN showed the best cell adhesion, proliferation and antibacterial activity. Ag/Ca co-implantation helps cells overcome bacteria and occupy the sample surface.